BIOFEEDBACK-ASSISTED RELAXATION AND PROGRESSIVE MUSCLE RELAXATION POTENTIAL FOR ENHANCING STUDENTS’ DISTRESS TOLERANCE - Jarasiunaite, Gabija; Perminas, Aidas; Gustainiene, Loreta; Peciuliene, Ieva; Kavaliauskaite-Keserauskiene, Ruta (European Scientific Journal, ESJ, 2015)
This study is aimed at assessing biofeedback-assisted relaxation and progressive muscle relaxation potential for enhancing distress tolerance in students’ population. 125 female undergraduate students aged between 18 and 27 participated in the study. Distress Tolerance Scale was used to evaluate distress tolerance. Participants of a study were randomly assigned into 3 different groups: 1) weekly biofeedback-assisted relaxation (n=40), 2) weekly progressive muscle relaxation training (n=43), and 3) comparison group without relaxation (n=42). The results of the study showed that biofeedback-assisted relaxation and progressive muscle relaxation were effective in enhancing students’ distress tolerance. Progressive muscle relaxation helped to enhance distress tolerance for those students whose initial distress tolerance was low. Biofeedback-assisted relaxation helped to enhance distress tolerance in students with higher level of perceived stress.